Evaluating the Reserves for Reducing Cancer Mortality by Avoidable Deaths in Moscow - A. A. Savina (Здоровье мегаполиса)
Background. Oncological diseases significantly contribute to the overall female mortality, so it is crucial to evaluate the reserves for reducing mortality from neoplasms in Moscow. Avoidable mortality includes the cases that could have been avoided with timely diagnostics, adequate treatment, and preventive measures.Objective. To identify the main causes of death from neoplasms among the Moscow female population, which could be avoided by organizing medical care and introducing new technologies, methods, and educational programs.Materials and methods. The authors used the official data of the Federal State Statistics Service of the Russian Federation (ROSSTAT) on deaths by causes of death according to several nosological entities and the ICD-10 chapter for neoplasms, all of which were defined as the initial causes of death in women in general and in certain age female groups in particular.Results. Despite the overall decrease in cancer mortality, malignant neoplasms remain the second leading cause of death. Currently, a steady trend of reducing avoidable mortality has been observed in Moscow. In 2022, malignant neoplasms mostly contributed to the avoidable cancer mortality in the Moscow female population (0-85 years): breast (C50) – 16.7%; colon (C18) – 11.3%; pancreas (C25) – 9.0%; stomach (C16) – 7.5%; trachea, bronchus and lung (C33-C34) – 7.1%; rectum (C20) – 4.9%.Conclusion. The analysis of the structure of cancer mortality in the Moscow female population showed that malignant neoplasms of reproductive system contributed the most. Thus, it is critical to analyze the reserves based on avoidable deaths from neoplasms among women in Moscow and then to develop targeted measures for improving the health of citizens and reducing the mortality rate in Moscow.